Empowerment of Productive Youth Groups in Forming Joint Businesses Based on Product Manufacturing in Tembung Village, Percut Sei Tuan District, Deli Serdang Regency - Hatta Ridho; Nurman Achmad; Husni Thamrin (Jurnal Pengabdian Masyarakat Bestari, 2023)
Empowering young people to start businesses with new and innovative economic models that use technology can help the country's economy. The activity approach consists of lectures and discussions carried out in stages: preparation, introduction, lecture, discussion and evaluation. This Community Service Program has completed most of its stages with positive responses from teenagers of productive age in Tembung Village. This Community Service Activity is still in the planning/initiation stage. Programs and activities include: 1) activity coordination; 2) awareness seminars on the importance of empowering productive youth; 3) socialization of tools and materials as well as the process of making merchandise products; and 4) closing, assistance with operational equipment, and installation of signage. In terms of understanding, marketing, increasing community capacity, as well as facilities and infrastructure, future projects and activities must be more comprehensive and sustainable. In addition, to increase the production capacity of goods, follow-up is required during the marketing process.